The Lysophospholipid Acyltransferase Antagonist CI-976 Inhibits a Late Step in COPII Vesicle Budding - Brown, William J. (2008)
The mechanism of coat protein (COP)II vesicle fission from the endoplasmic reticulum (ER) remains unclear. Lysophospholipid acyltransferases (LPATs) catalyze the conversion of various lysophospholipids to phospholipids, a process that can promote spontaneous changes in membrane curvature. Here, we show that 2,2-methyl-N-(2,4,6,-trimethoxyphenyl)dodecanamide (CI-976), a potent LPAT inhibitor, reversibly inhibited export from the ER in vivo and the formation of COPII vesicles in vitro. Moreover, CI-976 caused the rapid and reversible accumulation of cargo at ER exit sites (ERESs) containing the COPII coat components Sec23/24 and Sec13/31 and a marked enhancement of Sar1p-mediated tubule formation from ERESs, suggesting that CI-976 inhibits the fission of assembled COPII budding elements. These results identify a small molecule inhibitor of a very late step in COPII vesicle formation, consistent with fission inhibition, and demonstrate that this step is likely facilitated by an ER-associated LPAT.